A study on critical successful factors (CSF) of Beverly Hotel and its relationship with company sales performance / Ana Mariani Musbi - Musbi, Ana Mariani (2010)
Critical Success Factors (CSF) is the critical factors or activities required for Beverly Hotel to ensure the success in the hospitality industry. Critical Success Factors have been used significantly to present or identify a few key factors that Beverly Hotel should focus on to be successful. The study will identify the critical success factors of Beverly Hotel and its relationship with company sales performance. In order to achieve this, a list of factors is identified for investigation. A study is carried out systematically to investigate the critical success factors of Beverly Hotel. The success factors are based on the feedback from the respondents. This research conducted to understand the relationship between critical successful factors (CSF) and sales performance. The aim of the study is to identify the critical successful factors of Beverly Hotel. The result shows the critical successful factors and its relationship with Beverly Hotel sales performance. The implications of this result lead to Beverly Hotel success in the hospitality industry.